Evolution and genetic diversity of atypical porcine pestivirus (APPV) from piglets with congenital tremor in Guangxi Province, Southern China. Issue 3 (13th December 2020) - Shi, Kaichuang; Xie, Shouyu; Sun, Wenchao; Liu, Huixin; Zhao, Jing; Yin, Yanwen; Si, Hongbin; Qu, Sujie; Lu, Wenjun
Abstract: Atypical porcine pestivirus (APPV) was identified and associated with congenital tremor (CT) type A‐II in new born piglets and has been reported in many countries. In China, the first APPV identification in swine herds was reported in Guangdong province in 2016. To investigate the genetic characteristics of APPV in Guangxi province, 53 tissue samples from neonatal piglets with CT were collected and detected from October 2017 to May 2019. Five APPV strains which were named as GX04/2017, GX01‐2018, GX02‐2018, GX01‐2019 and GX02‐2019 were obtained. Sequence analysis revealed that all six APPV strains from Guangxi province, including five strains from this study and one from a previous report, shared 83.3%‐97.5% nucleotide identity of complete genome and 91.7%‐99.1% amino acid identity of the open reading frame (ORF), and shared 77.7%‐97.7% nucleotide identity of complete genome and 90.6%‐99.3% amino acid identity of ORF with reference strains. Phylogenetic analysis indicated that all APPV strains could be divided into three clades based on the complete genome, N pro, E rns and E2 gene sequences, respectively; and the APPV strains from Guangxi province distributed in two clades (clades I and II). No sign of recombination was observed from Guangxi strains. Evolution analysis performed on the complete genome of 58 APPV strains showed that America, Europe and Asia strains during 2006–2019 evolved at a mean rate of 1.37 × 10 –4 substitutions/site/year, and the most recent common ancestor (tMRCA) of them was estimated as 1, 700.5 years ago. The findings of this study indicated that there existed a high degree of genetic diversity of APPV from Guangxi province, Southern China, which provided important information on the epidemiological features and evolutionary relationships of APPV. Abstract : The complete genomic sequences of five APPV strains were obtained from positive clinical tissue samples from neonatal piglets with CT in Guangxi province, Southern China. The five APPV strains distributed in two clades in phylogenetic trees based on complete genome, Npro, Erns and E2 gene sequences, respectively, which indicated that APPV strains from Guangxi province existed high degree of genetic diversity and variation. The results provided valuable information on epidemiological and evolutionary characteristics of APPV in Southern China.